SAP® BW : a Step-by-Step Guide - Fu, Ph. D.; Fu, P. E. (Addison-Wesley Professional, 2002)
SAP BW has recently come to the fore as a valuable tool for developing data warehouses that accurately and effectively support critical business decision making. It facilitates easy-to-use and high-performance extraction, transfer, transformation, and loading of data from a variety of data sources, including such comprehensive business management systems as SAP R/3. This practitioner's guide uses step-by-step instructions complete with a plethora of screen captures to illustrate key SAP BW functionalities. It demonstrates how SAP BW implements the fundamental star schema and solves the major challenges inherent in the creation of data warehouses: performance, reliability, and error-handling. Using a real-world business scenario as a running example, SAP® BW presents a comprehensive view of the technology, from underlying concepts and basic techniques through its most sophisticated capabilities. Specific topics covered include: Creating an InfoCube and loading the data Checking the accuracy of data with BW Monitor and the Persistent Staging Area (PSA) Creating queries to generate reports using Business Explorer (BEx) Managing user authorization with the Profile Generator Advanced InfoCube design techniques Aggregates and multicubes Working with the Operational Data Store (ODS) Installing business content and creating an R/3 source system in BW Loading data from SAP R/3 into SAP BW Data maintenance Performance tuning, including parallel query option and data packet sizing Object transport Although the focus is on the core SAP BW technology, this book also discusses other relevant technologies, including Basis, ABAP (Advanced Business Application Programming), ALE (Application Link Enabling), and ASAP (Accelerated SAP) for BW. With the clear explanations and practical techniques presented in SAP® BW information systems professionals will gain both the general understanding and specific skills necessary to create high quality data warehouses that support effective decision making. 0201703661B07092002.